2022
DOI: 10.3390/app122311989
|View full text |Cite
|
Sign up to set email alerts
|

How K12 Teachers’ Readiness Influences Their Intention to Implement STEM Education: Exploratory Study Based on Decomposed Theory of Planned Behavior

Abstract: Teachers are the key factors in ensuring the effectiveness of STEM education, and their intentions deeply influence their teaching practices. The existing research about the influencing factors of teachers’ intentions to implement STEM education has some problems, such as small sample sizes, being limited to teachers of a single subject, and the need for optimization of the theoretical model relied on. This research, based on the decomposed theory of planned behavior combined with the readiness of teachers, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…A study by Abdullah et al (2017) measured three aspects of STEM teaching readiness among 190 Malaysian science and mathematics teachers, including cognitive readiness (i.e., the readiness of a teacher to think creatively and critically design a concept to solve problems), affective readiness (i.e., the continuum of emotional readiness of teachers [positive, neutral, and negative] to carry out their duty), and behavioral readiness (i.e., the actual knowledge and skills of teachers in doing something new) (p. 7). Related thereto, a study by Wu et al (2022) found that affective readiness…”
Section: Introductionmentioning
confidence: 91%
“…A study by Abdullah et al (2017) measured three aspects of STEM teaching readiness among 190 Malaysian science and mathematics teachers, including cognitive readiness (i.e., the readiness of a teacher to think creatively and critically design a concept to solve problems), affective readiness (i.e., the continuum of emotional readiness of teachers [positive, neutral, and negative] to carry out their duty), and behavioral readiness (i.e., the actual knowledge and skills of teachers in doing something new) (p. 7). Related thereto, a study by Wu et al (2022) found that affective readiness…”
Section: Introductionmentioning
confidence: 91%
“…Wu and coworkers [12] in their paper, How K12 Teachers' Readiness Influences Their Intention to Implement STEM Education: Exploratory Study Based on Decomposed Theory of Planned Behavior, examine the factors that affect K12 teachers' intentions to implement STEM education in China. Using a decomposed theory of planned behavior combined with teacher readiness, the authors developed an assumption model of the factors influencing teachers' STEM education intentions.…”
Section: Innovative Pedagogies In Steam Educationmentioning
confidence: 99%
“…For instance, a study by Roy et al (2022) and Chai et al (2020) indicated that perceived behavioral control was the best predictor of both science teachers' and students' intentions to employ AI in the educational setting. The availability of resources (Gado et al, 2022), the degree of training (Wu et al, 2022), and the perceived usability of AI (Yan et al, 2014) are only a few examples of the variables that can affect perceived behavioral control. Academics are more likely to plan to use artificial intelligence (AI) in their teaching when they feel they have the tools, education, and expertise to do so.…”
Section: Relationship Between Perceived Behavioural Control and Inten...mentioning
confidence: 99%